Suara Terbanyak dan Kualitas Anggota DPRD Provinsi DIY (Implementasi Putusan MK No. 22-24/ PUU-VI/2008 dalam Pemilu 2009) - Pusat Kajian Konstitusi dan Pemerintahan FH-Universitas Muhammadiyah Yogyakarta (Jurnal Konstitusi, 2016)
The implementation of the Constitutional Court Decision No. 22-24/ PUU-VI/2008 about counting majority votes  in  2009  legislative  elections  in the province of DIY has a significant effect. considering the system used in the vote count to determine the members of both national and local legislatures are new and very different from previous elections. However, these effects are not caused major problems, because before the election day, the decision has been disseminated by each political party internally and implemented by Electoral Commission. Although the Constitutional Court decision issued after a waiting list of legislative candidates have been announced by the KPU.